Antivenomic approach of different Crotalus durissus collilineatus venoms - Isadora Sousa de Oliveira (Journal of Venomous Animals and Toxins including Tropical Diseases, 2018)
Abstract Background Our group has previously performed a proteomic study verifying that individual variations can occur among Crotalus durissus collilineatus venoms. These variations may lead to differences in venom toxicity and may result in lack of neutralization of some components by antivenom. In this way, this study aimed to evaluate the Brazilian anticrotalic serum capacity in recognizing twenty-two Crotalus durissus collilineatus venoms, as well as their fractions. Methods The indirect enzyme-linked immunosorbent assay (ELISA) was chosen to evaluate the efficacy of heterologous anticrotalic serum produced by Instituto Butantan (Brazil) in recognizing the twenty-two Crotalus durissus collilineatus venoms and the pool of them. Moreover, the venom pool was fractionated using reversed-phase fast protein liquid chromatography (RP-FPLC) and the obtained fractions were analyzed concerning antivenom recognition. Results Evaluation of venom variability by ELISA showed that all venom samples were recognized by the Brazilian anticrotalic antivenom. However, some particular venom fractions were poorly recognized. Conclusion This study demonstrated that the Brazilian anticrotalic serum recognizes all the different twenty-two venoms of C. d. collilineatus and their fractions, although in a quantitatively different way, which may impact the effectiveness of the antivenom therapy. These results confirm the need to use a pool of venoms with the greatest possible variability in the preparation of antivenoms, in order to improve their effectiveness.